Women’s attitudes towards abortion-rights movement in Poland: the role of sexism and right-wing authoritarianism: Sexism & Abortion Rights Movement - Dominiak-Kochanek, Monika; Rajchert, Joanna; Konopka, Karolina (Society Register, 2025)
The present study was inspired by the mass anti-government demonstrations organized by women after the further tightening of abortion laws in Poland. As a result, salient social polarization emerged with a clear-cut division for these who contested marches against near-total abortion ban and those who supported them. In female participants (N = 291), we examined the role of two forms of sexism and right-wing authoritarianism in predicting an attitude towards the abortion-rights movement. In line with the hypotheses, the results showed that right-wing authoritarianism was responsible for the relationship between sexism and attitudes toward the abortion-rights movement. Benevolent and hostile sexism were negatively related to the attitudes toward the abortion-rights movement, but this relationship was partly explained by right-wing authoritarianism. Our findings suggest that targeting right-wing authoritarianism might be crucial for changing the beliefs underlying both forms of sexism and attitudes toward abortion movement. It seems particularly important regarding benevolent sexism still mistaken for protection rather than an ideology patronizing women and preserving gender inequality.